Mapeamento da fragilidade potencial do alto curso da Bacia Hidrográfica Do Rio Cotegipe - PR - Grisa, Kleitson Telmo (2014)
This research aims to develop a mapping of the potential fragility of the upper course of the river Cotegipe in the City of Francisco Beltrão in the State of Paraná. Increasingly it is necessary an integrated study of the natural environment , where the elements that are present in that region are covered, so that the results are most near reality. Thus , this study provides reliable data on the upper course of the river Cotegipe with regard to conservation of the natural environment. To perform the mapping of the potential fragility of the upper course of the river was necessary to analyze the physical boundaries of the study area, slope classes and soil types . The methodology for this research is based on the concepts of analysis of potential frailty proposed by Ross (1994). Maps hypsometric, slope , land use and soil were obtained based on Elevation Aster Gdem V2 with a resolution of 30 m , found on the website www.gdem.aster.ersdac.or.jp. The results showed a relative environmental balance in the upper course of the river area Cotegipe explained more fully by the forms of land use properly than to natural factors present in the area . The knowledge provided by research serves as a basis for planning the interference in the actions performed on the conservation and exploitation of the area that makes up the upper course of the river Cotegipe